2022
DOI: 10.1186/s12889-022-14290-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of accessing HIV services for street-involved youth in Canada and Kenya

Abstract: Introduction UNICEF estimates that there are as many as 100 million street-involved youth (SIY) globally. Marginalized conditions put SIY at higher risk of HIV and adverse outcomes once HIV-positive. The objective of this analysis was to describe barriers and facilitators of accessing HIV prevention, testing, and treatment services as Phase I of an implementation study evaluating the use of peer navigators to increase access to HIV services. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The reason for the lack of using this source might be that homeless people may have more difficulty in accessing a primary care physician or preventive healthcare services and in obtaining health information; therefore, there is a lack of opportunity to improve their level of knowledge. This is consistent with the broader literature showing that the physician-patient relationship acts as a barrier for underserved communities, and such individuals may access healthcare services less often [47][48][49] as well as the observation that the COVID-19 pandemic has negatively affected access to health-related information and sources of healthcare worldwide [50][51][52][53]. On the other hand, the surveyed respondents indicated that the most common information resources used were mass media and the internet.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for the lack of using this source might be that homeless people may have more difficulty in accessing a primary care physician or preventive healthcare services and in obtaining health information; therefore, there is a lack of opportunity to improve their level of knowledge. This is consistent with the broader literature showing that the physician-patient relationship acts as a barrier for underserved communities, and such individuals may access healthcare services less often [47][48][49] as well as the observation that the COVID-19 pandemic has negatively affected access to health-related information and sources of healthcare worldwide [50][51][52][53]. On the other hand, the surveyed respondents indicated that the most common information resources used were mass media and the internet.…”
Section: Discussionsupporting
confidence: 87%
“…Most respondents reported poor AHD screening coordination among implementers due to communication challenges owing to the absence of ground telephone system and other social platforms for communicating and sharing relevant AHD updates. Communication system barriers existing between healthcare providers and their clients have also been documented elsewhere [24]. Thus, the use of social mobile platforms (SMPs) with instant messaging applications such as WhatsApp is highly recommended.…”
Section: Discussionmentioning
confidence: 98%
“…AHD services could also be integrated into ART and TB programmes which are well established and su ciently supported by MoH PEPFAR implementing partners. Integration of related health programs reduces duplication of services, is cost-effective, and as well as e cient [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other studies showed that COVID-19 pandemic resulted in fear and low motivation to use health services and maintain adherence. This lack of motivation was due to low income and hunger, which took priority over adherence to appointments and medications [36,37]. Nevertheless, for some other participants, their motivation to use HIV care services was not affected by the pandemic.…”
Section: Discussionmentioning
confidence: 99%